Buried together : a story of quarantine and a question of conscience - Clair, Robin Patric (Social fictions series, 2021)
"Based on the true story of Silas Mercer Beasley Jr., a Civil War conscientious objector. Silas Jr.'s brothers fought for both sides (Union and Confederacy) and a few questioned Silas' courage. Following the war, he and his Union veteran brothers faced threats of death from local Southerners. Silas gathered his family and left Georgia in pursuit of his missing brothers and safety. All but Silas fell ill during this exodus due to the pandemic (i.e., smallpox, typhoid fever, measles). They sought refuge in a cabin in Tennessee where they quarantined through these troubling times. During their quarantine, Silas' mother told the story of the Cherokee Removal and the infamous Kilakeena Elias Boudinot to help her son keep vigil so that he might protect the family from marauders. Surrounded by danger, Silas Jr. was faced with more than one life and death decision and more than one heart-breaking loss. This historical novel speaks to contemporary issues. Based on archival documents and Silas Jr.'s published diary accounts of the Civil War times and beyond, readers learn of conscription, bi-racial families, and voter suppression. With respect to the Cherokee Removal, readers learn about the culture as depicted through the ethnographic work of James Mooney. They further learn of various Generals' opposition to the Cherokee Removal and political strategies of Jackson and Van Buren. But more than this, readers learn of the life experiences of one family, and of one man; the heartbreak they endured and the resilience they displayed"--